Examination of the effects of design-oriented STEM activities on the 21st century skills of pre-school children aged 3-4 - Yalçın, Vakkas; Öztürk, Oğuzhan (Southeast Asia Early Childhood Journal, 2022)
In this study, the effects of D-STEM activities on the 21st-century skills of pre-school children aged 3-4 were investigated. The research was carried out in a mixed design, both quantitative (experimental design with experimental and control groups (N:84) with pretest-posttest and retention test) and qualitative (observation and researcher diary). To test hypothesis four, serial 3 (time: pre-test, post-test, and follow up) x2 (experiment group and control group) mixed factorial analysis of variances (ANOVA) was used. As a result of the research, it was observed that D-STEM activities permanently increased the total dimension of the 21st century and all sub-dimensions of Life and Career Skills, Learning and Innovation Skills in the experimental group children. In addition to these, it was concluded that the qualitative findings obtained within the scope of the research supported the quantitative results of the study. On the other hand, it was concluded that there was no statistically significant difference between the sub-dimensions and total scores of the 21st century skills pre-post and permanence tests of the children in the control group. It was concluded that the D-STEM activities carried out permanently increased the 21st century skills of the experimental group children. In line with the results of the study, preschool teachers can contribute to the multi-faceted development of children by doing more activities related to STEM education and Design Thinking Model.